Tizanidine: Advances in Pharmacology & Therapeutics and Drug Formulations - Zhu LL; Wang YH; Zhou Q (Journal of Pain Research, 2024)
Ling-Ling Zhu,1,* Yan-Hong Wang,2,* Quan Zhou2 1VIP Geriatric Ward, Division of Nursing, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People’s Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quan Zhou, Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Jiefang Road No. 88, Shangcheng District, Hangzhou, Zhejiang Province, 310009, People’s Republic of China, Email zhouquan142602@zju.edu.cnBackground: Skeletal muscle relaxants (SMRs) are widely used in treating musculoskeletal conditions. All SMRs, with the exception of baclofen and tizanidine, are on the list of 2023 American Geriatrics Society Beers Criteria® for potentially inappropriate medication use in older adults. In our geriatric practice, off-label use of tizanidine as preemptive analgesia drove us to find recent advances in its pharmacology and therapeutics. An update review of tizanidine was thus presented, aiming to bring the latest knowledge to clinicians and promote further research and practical exploration.Methods: Relevant literature up to December 2023 was identified through searches of PubMed, Web of Science, and Embase.Results: Tizanidine, a centrally acting alpha-2 adrenoceptor agonist with both antispastic and antispasmodic activity, shows efficacy in the common indications for all SMRs. From the perspective of drug safety, tizanidine has lower incidences of adverse events (injury, delirium, encephalopathy, falls, and opioid overdose) compared to baclofen, no association with risk of Alzheimer’s disease as with orphenadrine, no risk of serotonin syndrome like metaxalone when comedicated with serotonergic drugs, no significant pharmacokinetic changes in CYP2C19 poor metabolizers unlike diazepam and carisoprodol, and no physically addictive or abuse properties like carisoprodol and diazepam. From the perspective of new and potential therapeutic uses, tizanidine has additional benefits (eg, gastroprotection that can improve patient tolerance to nonsteroidal anti-inflammatory agents, anti-neuropathic pain, a key component of multimodal analgesia strategy to reduce early postoperative pain, and anti-tumor effects). New delivery systems of tizanidine are developing to improve the pharmacokinetics of oral products, including buccal patches, transdermal delivery systems, nasal spray, and in situ rectal gel.Conclusion: Tizanidine is an SMR with unique features and may be an optimal initial choice for older adults. There would be more scientific studies, wider therapeutic applications, and new drug formulations in the future.Keywords: musculoskeletal pain, skeletal muscle relaxants, neuropathic pain, older adults, tizanidine